SEARCH ENGINES IN COLOMBIA: LEGAL REVIEW AND STUDY OF THE MUEBLES CAQUETA VS. GOOGLE INC CASE - Peralta, Sarah Osma (Law, State and Telecommunications Review, 2020)
Purpose ”“ Considering the relevance of personal data protection, this article focuses on the identification of the criteria used by Colombian Courts regarding the rights to access, modification and erasure personal data within the context of information made available through search engines. This framework will expose the different cases ruled by the Colombian Constitutional Court as it attempts to highlight which were the criteria used by the courts that brought them to rule that search engines are mere intermediaries between the content makers and data subjects. Finally, this study aims to contribute not only to the data protection legal literature in Colombia, but also, to improve the possibilities to effectively implement user´s rights of online search engines in Colombia. Methodology ”“In order to achieve the purpose of this research project, the following methodological strategies will be employed: (i) Legal-analytical study, by way of reviewing the Colombian regulatory framework in order to map out main rules regarding the fundamental rights to access, modification and erasure of personal data, and determining which ones are the aspects hindering the effective implementation of the rights; (ii) Legal-theoretical study, where it reviews the issues identified by legal scholars as hampering the implementation of data protection rights in general; (iii) Legal-empirical study that aims to raise awareness regarding the incidence of the activities carried out by search engines in the life of data subjects. Findings ”“ The Colombian Constitutional Court has seen search engines as mere intermediaries, meaning they do not have to rectify, correct, eliminate or complete the information listed in the results they provide. This approach demands that the Judiciary enforces the existence of a right to request the erasure of links and the need of procedures provided by them to do it effectively without erasing or altering the content of the website. This delisting process should not be arbitrary based on conditions that allow data subjects to ask the erasure of links associated with their names. In the European Union, the conditions to get those results delisted are inadequacy, irrelevance, or excessiveness in relation to the processing purposes. The current position of the Constitutional Court about the search engines role and their responsibilities has not protected the user’s fundamental rights to privacy, reputation, and honor. Therefore, a more committed study on behalf of the Court is required. Practical Implications ”“ In the Muebles Caquetá Case, the Court must point out the importance of the activities carried out by online search engines, and force them to face the implications of being a “controller” of the processing of personal data that takes place within their services. I suggest that the Court itself should draft clear delisting guidelines considering the opinions of a group of impartial experts, civil society representatives and the local Data Protection Authority. Originality ”“ Considering the implications posed by personal data and data mining, this article identifies the legal and regulatory framework surrounding those activities and in way contribute to create a data protection culture in Latin America, raise awareness regarding the incidence of search engines in the life of data rights holders, identify possible disconnections between the existent regulatory framework for personal data rights, and facilitate the cooperation between Courts and stakeholders of the telecommunication and media sectors, based on the common goal of fulfilling the public interests of ensuring data protection rights.